A bibliometric analysis of vaccine research on Chikungunya virus: contributors, trends, and emerging frontiers - Shao, Da; Kou, Zengwei (Frontiers in Immunology, 2025)
Chikungunya virus (CHIKV), the causative agent of CHIKV fever, is an arthritogenic alphavirus belonging to the Togaviridae family. It is primarily transmitted by Aedes aegypti mosquitoes and has the potential to become a globally pandemic pathogen. Infection with CHIKV typically results in high fever and often debilitating, sometimes chronic polyarthralgia, as well as central nervous system complications. To date, only few highly effective drugs available for treating CHIKV infection or controlling its replication and transmission. Immunotherapeutic strategies and vaccine development are considered promising approaches, particularly nucleic acid-based vaccines, which offer the advantages of rapid development, high efficacy, and precision. In this study, we performed a bibliometric analysis (the literature search was conducted up to June 2025) using data from three major medical databases to explore research trends, geographic and institutional distribution, and key research hotspots in the field of CHIKV immunotherapy and vaccine development. Our findings reveal a rapidly growing body of literature with significant contributions from leading research institutions in the United States, particularly the University of Texas system. Among the various vaccine types studied, live-attenuated vaccines and nucleic acid-based vaccines dominate the field, with the latter showing a marked increase in research attention in recent years.